Numerical Investigation On The Effects Of Geometrical Parameters On Film Cooling Performance - Ali, Amir Hussein (2013)
The aim of this study is to investigate the effect of different kinds of cooling holes and staggered arrangements on adiabatic and conjugate film cooling effectiveness for convex surface of gas turbine blade. The investigation included a new cooling hole scheme called heart-shaped to solve the vortex problem claimed to be responsible for the detrimental lift-off phenomenon in conventional simple cylinder film cooling holes. Also, the conjugate studies included a new conjugate blade technique called multi-layers to be helpful in speeding up the heat absorption from the upper blade surface. Fluent® has been utilized and realizable κ-